LONG JUMP: THE ARE BODY HEIGHT AND BODY WEIGHT GOOD PREDICTORS OF PERFORMANCE IN ELITE JUMPERS? - RATKO PAVLOVIĆ; ZHANNETA KOZINA; Simeonov, Aleksandar (Slovak Journal of Sport Science, 2022)
Background: Long jump are cyclic-acyclic movements of maximum intensity. It is a discipline that combines speed and jump in technique, that is, the speed-strength properties of competitors. Speed, agility and explosiveness are of special importance in jumpers. The main goal of the research is to determine the influence of Body height (BH) and Body weight (BW) with the best achieved results of Long jump. Material and methods: In study included 21 top male jumpers (BH=184.19±4.68cm; BW=78.86±6.81kg). Their achieved best results were analyzed. Pearson correlation coefficient was used to determine the relationship between body height and body weight and the results of long jumpers. Univariate model of regression analysis was applied and the relevant coefficients were calculated. The level of acceptance of statistical significance was set to p<0.05. Results: Simple regression analysis did not show a statistically significant effect of Body height on the results in the long jump (BH vs. Long jump R=0.183; p>0.05), while Body weight confirmed a significant inverse relationship with the results of the jump (BW vs. Long jump R= - 0.442; p<0.05). Conclusion: Long jumpers contain a large percentage of active muscle mass that integrates and generates motor explosive abilities for the success of long jumpers, primarily strength and speed, which is confirmed by the results of the study. However, a good jump technique is also necessary, but with optimal body weight, because any increase in weight has a negative effect on the length of the long jump.
Keywords: anthropometric characteristics; elite jumpers; influence; long jump